Evaluation of methods for 3D imaging and analysis of vascularisation in biopreparations - Zöller, Nora; Franke, Lisa; Claussen, Joelle; Gerth, Stefan; Rauh, Cornelia; Radlanski, Ralf J.; Hiller, Karl Heinz; Hildenbrand, Markus F.; Wittenberg, Thomas; Hufnagel, Eva (Current Directions in Biomedical Engineering, 2022)
Motivation: Within the field of bio-implants one topic deals with the in-vitro production of 3D tissues from cell cultures. A major challenge in the cultivation of biopreparations is the imitation of the vascular system with its surrounding tissue. Additiv manufacturing of such vascularisation could be supported with an adequate template from high-resolution 3D radiographs. Goals: Evaluation of high-resolution 3D-imaging methods and 3D-analysis approaches to extract the vascularisation from tissue samples. Methods: To provide such template, vascular structure of small tissues samples (partially treated with contrast medium) were recorded and compared using high-resolution CT and MRI imaging modalities. Optimal measurement parameters were selected for the acquisition of very small vessels. Interactive and semi-automated segmentation of the vessel system were investigated and compared. Results: MRI scans yield a higher contrast than CT scans, but are much slower. Duration of interactive segmentation ranges between 1 to 12 hours. Runtime of the (semi) automatic method was between 5 and 20 minutes, not counting manual adjustment of the parameters. Correlation between manual and automatic segmentation yield Hausdorff distances of 0.024 (CT) and 0.74 (MRI) and Dice coefficients of 0.7 (CT) and 0.39 (MRI). Conclusion: Both imaging methods are appropriate for high-resolution vessel detection and segmentation, nevertheless, MRI with no contrast agent seems preferable if the imaging time can be reduced.
CRIS-Team Scopus Importer:2022-09-30
Keywords: 3D-reconstruction; Bio-imaging; CT; MRI; Vascularisation